The Epidemiological Trends of Primary Benign and Malignant Bone Tumors in Iran - Salarvand, Samaneh; Abdollahi, Alireza; Shams Ardekani, Shireen; Mortazavi, Seyed Mohammad Javad; Nazar, Elham (Asian Pacific Journal of Cancer Biology, 2024)
Background & objective: The incidence of various tumors is strongly influenced by racial characteristics, and therefore the distribution of benign and malignant lesions follows different epidemiological and pathophysiological patterns in the societies. This study aimed to evaluate the epidemiological trend of primary benign and malignant bone tumors in the Iranian population. Methods: In this cross-sectional study, epidemiological and pathological information related to cases of benign and malignant primary bone tumors registered in the data registry of pathology laboratory of Imam Khomeini Complex hospital in Iran between 2017 and 2022 were assessed. Including criteria was all patient with established pathology diagnosis of bone tumors and excluding criteria was patients with incomplete data. Results: In total, 617 primary bone tumors (233 benign lesions and 384 malignant lesions) were assessed within 5 years between 2017 and 2022. The average age of patients in benign and malignant lesions subgroups was 29.50±16.95 years and 35.30±19.70 years respectively with the highest incidence in the second and third decades of life in both lesion types. Overall, 52.8% of benign tumors and 58.9% of malignant tumors were found in men. The most frequent benign tumors reported in the study periods including osteochondroma found in 30.5%, and enchondroma in 29.2%. Of malignant bone tumors, osteosarcoma was the most prevalent type with an overall prevalence of 32.6% followed by chondrosarcoma (20.8%) and Ewing sarcoma (16.7%). In the case of benign tumors, a decrease in the trend during the last four years was showed, while the trend of malignant tumors was completely upward in the last four years. Conclusion: The epidemiological distribution of primary benign and malignant bone tumors in Iran is similar to global statistics, but with a downward trend in benign masses and vice versa, an increasing trend in malignant tumors in recent years.